2009
DOI: 10.1126/science.1169806
|View full text |Cite
|
Sign up to set email alerts
|

Elevated CO 2 Enhances Otolith Growth in Young Fish

Abstract: A large fraction of the carbon dioxide added to the atmosphere by human activity enters the sea, causing ocean acidification. We show that otoliths (aragonite ear bones) of young fish grown under high CO2 (low pH) conditions are larger than normal, contrary to expectation. We hypothesize that CO2 moves freely through the epithelium around the otoliths in young fish, accelerating otolith growth while the local pH is controlled. This is the converse of the effect commonly reported for structural biominerals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
148
5
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 197 publications
(159 citation statements)
references
References 7 publications
3
148
5
3
Order By: Relevance
“…area, and density in larval fish and expand upon previous reports of increased otolith size measured using 2D microscopy techniques (10,(20)(21)(22).…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…area, and density in larval fish and expand upon previous reports of increased otolith size measured using 2D microscopy techniques (10,(20)(21)(22).…”
Section: Resultsmentioning
confidence: 93%
“…Although otoliths (ear stones) are an important part of the auditory and vestibular sense organs in fishes (19), their formation under ocean acidification conditions has received limited attention. Previous studies of larval fish otoliths have identified consistent ocean acidification effects across some species, but have been constrained by the use of 2D measures of size, which limits further analysis of sensory consequences and the ability to examine the full extent of ocean acidification impacts (20)(21)(22). With this in mind, we used high-resolution microcomputed tomography (micro-CT) to measure the 3D size and density of otoliths in fish larvae raised under acidified conditions (Fig.…”
mentioning
confidence: 99%
“…This latter is bathed in extracellular fluids with their particular controlled carbonate chemistry and surrounded by the shell forming an epithelium (Appellöf 1893). Similarly, hypercalcification has also been observed in the internal otoliths of fish (Checkley, 2009), a structure bathing inside a fluid chamber and regulating fish equilibrium. Shiao et al (2005) postulate that calcification conditions are maintained around the otolith by the ion-transporters discovered on the external membrane.…”
Section: Discussionmentioning
confidence: 98%
“…Comeau et al 2011) or echinoderms (reviewed by Dupont et al 2010). Some studies however reported unchanged or increased calcification rates under high seawater pCO 2 in echinoderms (Wood et al 2008;Gooding et al 2009;Ries et al 2009), decapod crustaceans (Ries et al 2009), juvenile cephalopods (Gutowska et al 2010a,b), and teleost fish (otholiths: Checkley et al 2009;Munday et al 2011). Walsh (2001, 2003) and Seibel and Fabry (2003) hypothesized that adults or juveniles of active species with high metabolic rates are not impaired as negatively by ocean acidification as species with lower metabolic rates.…”
Section: Introductionmentioning
confidence: 99%
“…By contrast, fish were initially believed to be safe from the effects of OA, as early studies demonstrated a lack of mortality under extremely high CO 2 levels (greater than 10 000 matm) [5]. However, an increasing body of evidence suggests that OA-relevant CO 2 /pH levels induce various sublethal effects in fish, including otolith over-growth [6,7], a shift in behavioural lateralization [8,9], alterations in olfaction that affect detection of cues from substrates, parents [10], prey [11] and predators [8,12,13], and impaired learning [9,14]. Because the gamma-aminobutyric acid type A (GABA A ) receptor antagonist, gabazine, restores proper discrimination of predator odour, learning of predatory cues [14] and behavioural lateralization in OA-exposed fish [8], at least some of the deleterious effects of OA in fish seem to be related to altered neurotransmitter function.…”
Section: Introductionmentioning
confidence: 99%